2013
DOI: 10.1002/pssb.201300082
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring morphologies of diamond thin films for neural stem cells culturing

Abstract: Phone: þ420 220 318 482, Fax: þ420 220 318 468A controllable growth of neural cells and/or neural stem cells (NSCs) on artificial substrates is highly attractive scientifically as motivated by neurological and neurodegenerative disease treatment. In this contribution, we report on human fetal NSCs attachment and growth on the diamond films. Diamond films of different morphologies were deposited by linear antenna microwave plasma system from H 2 /CO 2 /CH 4 gas mixtures.We show that the employed NSC lines attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Several articles report on successful culturing of neural cells on nanocrystalline diamond 15,33,40 , ultrananocrystalline diamond 8,41 or nanodiamond treated substrates 42 without any form of additional chemical coating. Results of cultivation of uncoated substrates are summarized in 7 .…”
Section: Effect Of Chemical Treatment: Pei Pdl and The Role Of Lamininmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles report on successful culturing of neural cells on nanocrystalline diamond 15,33,40 , ultrananocrystalline diamond 8,41 or nanodiamond treated substrates 42 without any form of additional chemical coating. Results of cultivation of uncoated substrates are summarized in 7 .…”
Section: Effect Of Chemical Treatment: Pei Pdl and The Role Of Lamininmentioning
confidence: 99%
“…There were many studies on evaluating the influence of various parameters of diamond films on neuron interfacing, recently summarized in 7 . The studies focused on the effect of surface termination (hydrogen vs oxygen termination 31 ), level of doping 32 , and surface morphology 1,33 . It is difficult to make general conclusions about the influence of one aspect or the other, as in some cases the results contradict each other.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, neurons have been patterned by contact micro-printing [29] as shown in figure 6, inkjet and laser patterning [24], selective seeding of NDPs [43] and diamond deposition on patterned carbon nanotubes [14]. Further studies showed that neuronal growth on various diamond and DLC substrates can be manipulated by a combination of laminin coating and surface termination [125][126][127]. Similarly, neuroblastoma cells have also been preferentially grown on UNCD patterned with O, F or H terminations, and this may lead to new routes to studying neuronal cancer [128].…”
Section: Diamond For Brain Researchmentioning
confidence: 99%
“…Thus, concerning the property of the material that can improve cell adhesion, it is worth considering the advantages of using functionalization of the substrate. H-, O-, and NH 2 -terminations of UNCD films have been shown to provide excellent substrates for insect circadian pacemaker neurons in comparison to untreated surfaces, while human fetal neural stem cells SPC-01 preferentially attach to the O- rather than to the H-terminated NCD surfaces. , In addition, adhesion of neuroblastoma cells or primary cortical neurons to DLC surfaces can be optimized using phosphorus-doped diamond-like carbon (P-DLC), rather than O-DLC termination or undoped DLC …”
Section: Interfacing Neurons With Dbms To Detect Action Potential Firingmentioning
confidence: 99%
“…H-, O-, and NH 2terminations of UNCD films have been shown to provide excellent substrates for insect circadian pacemaker neurons in comparison to untreated surfaces, while human fetal neural stem cells SPC-01 preferentially attach to the O-rather than to the H-terminated NCD surfaces. 97,98 In addition, adhesion of neuroblastoma cells or primary cortical neurons to DLC surfaces can be optimized using phosphorus-doped diamondlike carbon (P-DLC), rather than O-DLC termination or undoped DLC. 99 The roughness of the substrate may be also a relevant parameter.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%